Are vascular grafts at risk of occlusion after total hip replacement? A systematic review of the literature - Mancuso, Francesco; Di Benedetto, Paolo; Buttironi, Michele Mario; Gisonni, Renato; Frigatti, Paolo; Causero, Araldo (Acta Biomedica Atenei Parmensis, 2021)
Vascular complications during and after total hip replacement are relatively uncommon despite the close relationship between the involved structures. Previous surgical procedure of arterial reconstruction or substitution may be at higher risk of damage due to the modification in the anatomical landmarks or to the mechanical properties of the grafts different from native vessels. In literature few cases of graft occlusion or failure are reported during or soon after a total hip replacement. The aim of this review is to report them highlighting common features and risk factors